Impact of Dimension Stone Production on the Environment: A Case Study at Granites & Marbles Company Limited, Ghana. - Benin, Abraham Kwesi (2012)
A Thesis submitted to the Department of Materials Engineering, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the degree of Master of Science (Environmental Resources Management)